LEARNING WRITING SHORT STORY THROUGH SYNECTIC MODEL BASED ON STUDENTS’ CREATIVITY - Muliawan, Pondra; Nuryatin, Agus; Zulaeha, Ida (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Learning writing short story involves students? habitual behavior in composing creative writing, which is story about a character?s life that contains conflicts and resolution. In this case, teachers choose learning model which is suitable to the students? creativity. This study attempts to analyze the effectiveness of Synectic model based on students? creativity in 11th grade students of senior high school. This study used one group pre-test-post-test design. The samples were taken by using purposive sampling. The data were analyzed by using validity and reliability test. Meanwhile, in order to test the sample, normality and homogeneity tests were used. The final data analysis used paired t-test to know the comparison of the effectiveness of learning writing short story based on students? creativity. The results showed that learning writing short stories through Synectic model effectively affected students with high, medium, or low creativity. The average score of students with high, medium, and low creativity was 87.86, 81.56, and 78.38 respectively. The significance of this research is to be able to provide new insight in educational research and increase knowledge in learning composing short stories in educational institutions